2014
DOI: 10.1128/aem.03109-13
|View full text |Cite
|
Sign up to set email alerts
|

Commonly Used Disinfectants Fail To Eradicate Salmonella enterica Biofilms from Food Contact Surface Materials

Abstract: Salmonellosis is the second most common cause of food-borne illness worldwide. Contamination of surfaces in food processing environments may result in biofilm formation with a risk of food contamination. Effective decontamination of biofilm-contaminated surfaces is challenging. Using the CDC biofilm reactor, the activities of sodium hypochlorite, sodium hydroxide, and benzalkonium chloride were examined against an early (48-h) and relatively mature (168-h) Salmonella biofilm. All 3 agents result in reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(122 citation statements)
references
References 55 publications
1
114
1
6
Order By: Relevance
“…The biofilm forming ability of Salmonella on various surfaces, such as glass, stainless steel, polycarbonate, concrete, tile, acrylic and polystyrene, has been well documented [8][9][10][11][12]. However, most of these studies have focused on the impacts of environmental conditions on the later stage of Salmonella biofilm formation (at least after incubation for 24 h) and relatively little attention has been paid to its initial attachment which is one of the critical steps in the biofilm development.…”
Section: Introductionmentioning
confidence: 98%
“…The biofilm forming ability of Salmonella on various surfaces, such as glass, stainless steel, polycarbonate, concrete, tile, acrylic and polystyrene, has been well documented [8][9][10][11][12]. However, most of these studies have focused on the impacts of environmental conditions on the later stage of Salmonella biofilm formation (at least after incubation for 24 h) and relatively little attention has been paid to its initial attachment which is one of the critical steps in the biofilm development.…”
Section: Introductionmentioning
confidence: 98%
“…The microscopic appearance of Salmonella biofilm formed on the food processing surfaces changes over time. Morphologically more adherent and dense biofilm was observed by SEM at 168 h compared with 48 h on surfaces in food processing environments (Corcoran et al 2014). The SEM images in the present study provided evidence that isolates of Salmonella serovars recovered from layer farm environments are capable of attaching and forming biofilms on the eggshell surface.…”
Section: Discussionmentioning
confidence: 96%
“…However, in the present study, it was demonstrated that BC at 0.125% has an inadequate bactericidal effect against S. enterica serovar Typhimurium biofilm cells, resulting only in a 2-log reduction, whereas a sufficient 6-log reduction was achieved only with BC 0.25% (Table 2). Similarly, 0.02% BC failed to eradicate 48 h S. enterica serovar Typhimurium biofilm on concrete (only 0.22-log reduction) (66). It was also reported that BC 0.75% was required to eradicate 3-day biofilms of S. enterica serovar Typhimurium (65).…”
Section: Discussionmentioning
confidence: 99%